Measuring empowerment among people living with HIV: a systematic review of available measures and their properties. Issue 7 (3rd July 2019) - Cooper, Vanessa; Clatworthy, Jane; Harding, Richard; Whetham, Jennifer; ,
ABSTRACT: A systematic review was conducted to identify and appraise measures of empowerment used in peer-reviewed research with people living with HIV. Thirty articles reporting on 12 scales were identified via keyword and citation searches of electronic databases and hand searching of reference lists. The instruments captured a wide range of constructs, including self-efficacy, perceived knowledge/information seeking, self-management behaviours, belief in an active patient role and tolerance of uncertainty. While the majority of instruments were focused exclusively on self-efficacy to manage HIV, the Patient Activation Measure (PAM-13 and PAM-22) and the Health Empowerment Inventory were broader in scope. Most of the identified measures had acceptable construct validity, however there were insufficient data to determine the reliability or responsiveness of many of the scales. The findings highlight the need for a more concrete definition of empowerment and for further validation of existing measures with people living with HIV.